Sustaining the Craft of Traditional Iban Woodcarving of Sarawak, Borneo - Emmanuel, Osakue; Awangko' Hamdan, Awang Arshad; Doris, Maying (2025)
The determination of this paper is to examine the local Iban woodcrafts in Sarawak, Malaysia. The research is based on a comprehensive account of oral interviews, participatory observations, and literature review, which emphasizes the socio-historical background of indigenous Iban woodcraft as a political, social, and religious symbol. The same data are used to form a hypothesis about the techniques and materials used among Iban wood carvers and other traditional artists today. This research suggests strategies for invigorating and sustaining the indigenous Iban woodcrafts in Sarawak. To achieve this, effective techniques and methods of woodcrafts, as well as a faster and easier carving mechanism, were identified; knowledge of wood properties that guide the carver to the appropriate wood choice was acknowledged; and guidelines for sustaining and revitalizing Iban woodcrafts in Sarawak were analyzed.